PENGARUH LOCUS OF CONTROL DAN MORALITAS INDIVIDU TERHADAP KECENDRUNGAN KECURANGAN AKUNTANSI - I Gusti Agung Oka Kristina Dewi; I Wayan Sudiana; I Putu Deddy Samtika Putra (Hita Akuntansi dan Keuangan, 2021)
The tendency of accounting fraud is fraud caused by an error in reporting in financial reporting or an intentional act identical to corruption, misuse of assets and false questions. This study aims to determine the effect of internal variables locus of control, external locus of control and individual morality on the tendency of accounting fraud in OPD Badung Regency. This research was conducted using the results of a questionnaire instrument survey. The sample studied was 114 respondents with a purposive sampling technique using criteria. The results of hypothesis testing show that the internal locus of control and external locus of control variables have a significant effect on the tendency of accounting fraud, while individual morality does not have a significant effect on the tendency of accounting fraud in OPD Badung Regency